Guidance Note on Climate Change in Governance Operations (Washington, DC: World Bank, 2022)
Climate change is the consequence of market and governance failures. The World Bank Group’s climate change strategy, laid out in its 2025 Climate Targets and Actions, recognizes that governance will play a critical role in addressing climate change. The strategy commits the World Bank to support clients’ efforts to mainstream climate action and fully integrate climate change into their planning, budgeting and fiscal policies. The Governance Practice plays a leading role in the implementation of this strategy, through its work with center of government, planning and finance agencies, inter-governmental relations, governance of State-Owned Enterprises, and open government initiatives. This Note provides an overview of the Bank’s corporate climate change commitments and the application of these commitments in the Governance Practice. Annex 1 provides an illustrative list of climate change governance activities by business lines and identifies example projects. Annex 2 presents an illustrative list of Governance Climate Change indicators. Annex 3 provides additional information on climate co-benefits in projects with ICT and Gov-Tech activities.